New Differential Subordination and Superordination Results for a subclass of Meromorphic Univalent Functions Defined by a New Operator - Sabri, Mustafa A.; Atshan, Waggas Galib; El-Seidy, Essam (Iraqi Journal of Science, 2025)
In this paper, we explore and introduce a novel study employing a new operator denoted as W_(ν,γ,δ,τ,n,r,d)^(η,s) within the field of geometric function theory, particularly in the context of sandwich theorems. We derive results pertaining to differential subordination and superordination for this new formula operator. Additionally, we establish specific sandwich theorems.